MOLECULAR AND GENETIC MECHANISMS OF DEVELOPMENT OF CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA AND THEIR CORRECTION ALLIC BFM 2009 BY CYTOSTATIC THERAPY (World Science, 2021)
The aim of this study was to evaluate the prognostic value of the relationship between genetic abnormalities and clinical and laboratory parameters of peripheral blood and bone marrow in children with acute lymphoblastic leukemia (ALL).Material and methods. 105 children diagnosed with ALL were examined (average age 6 years). To detect chromosomal translocations AF4/MLL t(4; 11) (q23; p23), BCR/ABL t (9; 22) (q34; q11), E2A/PBX1 t (1; 19) (q23; p13) and TEL/AML t(12; 21) (q13; q22) the method of polymerase chain reaction with reverse transcription (RT-PCR) was applicated. PCR was performed with specific primers for the appropriate chromosomal aberrations. Detection of PCR products was performed by electrophoresis in 2% agarose gel. Determination of minimal residual disease (MRD) was performed by multiparameter flow cytofluorimetry using monoclonal antibodies.Results. Among patients, the incidence of ALL is most pronounced in children aged 3 to 6 years - 37 people (35.2%) and aged 6 to 9 years - 26 people (24.8%). The highest accidence was found among patients with chromosomal translocation TEL / AML - 22 (21%) of patients with a median age 5 years. In second place, the frequency of mutations is the translocation of E2A / PBX1. BCR / ABL translocation was less common - 1.9% of patients, but the expression of this gene indicates a bad course of the disease, as patients after cytostatic therapy under the ALLIC BFM 2009 program had a recurrence. Recurrence has also been observed in patients with TEL/AML chromosomal translocation.Determination of MRD showed its increased level in patients with chromosomal aberrations BCR / ABL and TEL/AML throughout the treatment phase. In addition, patients in these groups were diagnosed with initial leukocytosis followed by leukopenia after a course of chemotherapy. Patients of all groups showed a decrease in hemoglobin.Conclusion. The biggest changes in clinical and laboratory parameters were found between patients with chromosomal translocations BCR/ABL and TEL/AML, as evidenced by the development of relapses in patients of these groups. The low level of association between karyotype disorders, with the formation of AF4/MLL and E2A/PBX1, and clinical and laboratory parameters in patients with GLL may indicate that the isolated clonal disorders are independent prognostic factors for the course of the disease.